IMPLEMENTATION OF CURRICULUM MANAGEMENT THE LEARNING CENTER IN PAUD TERPADU MUTIARA YOGYAKARTA - Handayani, Iys Nur (Sunan Kalijaga International Journal on Islamic Educational Research, 2021)
Early childhood Education institutions that provide services and facilities to the students with the aim of the development aspects of the religion-moral, cognitive, language, social-emotional, and physical-motor. Proper learning model for early childhood is required. Centre learning models applied in the PAUD Institute need to have a curriculum management tailored to the curriculum that is carried out in an institution. The purpose of this article is to know the implementation of curriculum management in the Learning Center in PAUD Terpadu Mutiara Yogyakarta. The research method used in this study aims to obtain facts and conclusions in order to gain understanding, explanation, divination, and control. This type of research is a qualitative field research. Research in PAUD Terpadu Mutiara Yogyakarta. The result of this research is that the implementation of curriculum management in the Learning Center in PAUD Terpadu Mutiara Yogyakarta became the 4 stages of the processing process, as follows: 1) Planning curriculum is designed in accordance with vision, mass and institution objectives, 2) The organization of the curriculum contains the management of organizational in the institution, 3) Implementation of the curriculum in the Learning Centers (Preparation Center, Role of Micro Center, Macro Role Center, Beam Center, Faith and Taqwa Center, Arts Creativity Center, Science Center, Cooking Center, Multimedia Center, and Natural Material Center), 4) Control or appraisal is done in the students and all educators.